Developing and Validating a Scale for University Teacher's Caring Behavior in Online Teaching - Jing Zhao; Ling Zhang; Xiangquan Yao (MDPI AG, 2023)
Teacher caring behavior in higher education has been frequently studied in the context of face-to-face instruction. The COVID-19 pandemic has transformed the territory of high education such that synchronous or asynchronous online instruction has become an important component of college students' learning experience. The lack of valid and reliable scales makes it difficult to quantitatively examine teachers' caring behavior in online contexts. Building on existing literature, we designed and implemented a three-stage study that aimed to develop and validate a scale for measuring Chinese university teachers' online caring behavior from students' perspectives. Results from data analysis have shown that the scale has construct validity and internal consistency reliability. The scale has revealed that teacher caring behavior in an online context consists of three latent factors, namely, inclusiveness, support, and conscientiousness. This is consistent with the existing conceptualization of teacher care as a three-dimensional construct. The scale made targeted improvement of existing scales and can be used to quantitatively examine the relationship between teachers' caring behavior and students' academic performance, learning motivation, learning engagement, learning self-efficacy, sense of belonging, and mental health.